Negotiating power: examining the role of procedural elements in international peace talks - Coplen, M (2024)
Peace agreements don’t write themselves. They are negotiated — in complex, iterative sessions with highly contingent results. Diplomats take pains to establish a negotiation’s procedural elements (e.g., timing, venue, and rules of engagement) in advance; they often contest or adapt these elements throughout the negotiation process. This area of diplomatic practice is under-examined in International Relations (IR). Accordingly, this research explores the following questions: Do the procedural elements of negotiation impact the dynamics and outcomes of international peace processes? If so, how? This thesis argues that procedural elements have meaningful effects on negotiation dynamics and subsequent foreign policy outcomes; understanding these mechanisms is key to understanding ‘power’ in the international system. After critically examining existing theories of power in IR and identifying a crucial area of underdevelopment in the field’s construction of ‘agenda-setting power,’ this thesis advances the novel ‘Cubist concept of power.’ Inspired by the Cubist art movement, this conceptual framework highlights the multi-dimensionality, fragmentation, and perceptual relativity of power in negotiation contexts. This article-based thesis presents three discrete studies of illustrative procedural elements, adopting a pragmatic approach to research aims and methodologies. The first article leverages historical sources to assess US mediators’ use of time pressure tactics; the second uses a web-based survey to investigate the impact of ‘virtual venue’ selection during the COVID-19 pandemic; and the third draws on interviews with seasoned practitioners to explore the effects of notetaking practices. All three studies validate the influence of procedural elements in shaping negotiation dynamics and outcomes. Cross-cutting findings highlight the role of technological affordances, perceptions of procedural justice, and interpersonal relationship-building. This thesis complicates existing theories of power in IR while offering policy-relevant findings to support practitioners in designing more effective peace negotiations in the future.